CREATIVE INTERPRETATION OF CULTURAL HERITAGE AND HISTORICAL MONUMENTS BY UZBEK PAINTERS - Davlatova Nilufar Mansurovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores how Uzbek painters creatively interpret cultural heritage and historical monuments in visual arts. The study examines methods of integrating architectural and landscape elements, human activity, and symbolic representation into compositions. The works of prominent painters such as Chingiz Akhmarov, Malik Nabiev, and Rakhim Akhmedov are analyzed to demonstrate approaches to maintaining historical accuracy while enhancing artistic expression. The findings highlight the pedagogical, cultural, and aesthetic significance of using historical monuments as a resource for developing creative thinking and compositional skills in art education